Sex ratio potentially influence the complexity of social calls in Himalayan leaf-nosed bat groups - Gu, Hao; Sun, Congnan; Gong, Lixin; Zhao, Xin; Feng, Jiang; Luo, Bo; Jiang, Tinglei; Liu, Ying (Frontiers in Ecology and Evolution, 2023)
Animals living in a complex social environment emit diverse acoustic signals and thus serve as excellent subjects for understanding the evolution of acoustic communication. Previous studies have focused on the complexity of social calls in some group-living animals, yet the determinants of vocal complexity at the intraspecific level remain unclear. Here, we aimed to assess the influence of group composition on social call complexity in Himalayan leaf-nosed bats (Hipposideros armiger) in the non-breeding season. We divided bats into three groups with the same number of individuals but with different sex ratio compositions. We monitored social vocalizations for the all-male group, the all-female group, and the mixed group. We quantified vocal complexity for each group based on multiple acoustic metrics, including vocal repertoire, call sequences, the diversity index, and information capacity. The results showed that there were significant differences in the composition of call sequences among the three bat groups. The number of vocalizations was the highest in the mixed group, while the social call complexity was the highest in the all-male group, followed by the all-female group, and was the lowest in the mixed group. The results suggest that group composition of sex ratio potentially influence the vocal repertoire in Himalayan leaf-nosed bats. Our findings might provide a cue for vocalization research to investigate sex ratio in social groups as a potential driver for vocal complexity .